Association between serum 25‐hydroxyvitamin D and the effects of Angiotensin II receptor blocker on renal function among African Americans: A post hoc analysis of a randomized placebo‐controlled trial - Chen, Li (J Clin Hypertens (Greenwich), 2020)
We tested the hypothesis that vitamin D status may modify the effect of Angiotensin II receptor blocker (ARB) on renal function among African Americans. Sixty‐four participants were included in this ancillary study from a randomized, double‐blind, placebo‐controlled, crossover trial among normotensive African Americans to test the effect of ARB on stress response of blood pressure and renal sodium handling. The participants were randomly assigned to receive either ARB or placebo for one week, washed out for one week and then cross‐overed to receive the other intervention for one week. On the final day of each intervention, the participant underwent a mental stress test. Baseline serum 25‐hydroxyvitamin D [25(OH)D] level was measured in this ancillary study. Sixty‐four participants were included, aged 26.5 ± 10.2 years and 47% were female. Among the participants with the serum 25(OH)D concentrations in the low tertile, ARB treatment was associated with 2.58 mg/dL higher blood urea nitrogen (BUN) (P < .001) and was not associated with serum creatinine (SCr) or estimated glomerular filtration rate (eGFR) (Ps > .05). Among the participants in the high 25(OH)D tertile, ARB was associated with 1.59 mg/dL lower BUN (P < .001), 0.08 mg/dL lower SCr (P = .001), and 8.59 mL/min/1.73 m(2) higher eGFR (P = .001). The interactions between vitamin D and ARB on renal function were more significant during stress and recovery than at rest. The effects of ARB treatment on renal function are modified by the vitamin D status among African Americans. ARB may improve renal function only among the ones with optimal vitamin D status.